Proces tworzenia struktur państwowych na ziemiach II i III zaboru pruskiego przez polskie czynniki polityczne w latach 1806-1807 - Goclon, Jacek (Acta Universitatis Lodziensis. Folia Historica, 2005)
The years 1806-1807 were times of change in the history of the Polish nation. Military campaigns, that took place on the Polish ground were of much importance for the fortunes of Polish statehood. In 1806 Napoleon’s military forces entered central Europe and shortly afterwards destroyed the whole political establishment from 1795. Eleven years after the fall of the Commonwealth the issue of Polish independence known as "The Polish Question” remained very much alive. The Great Army was considerably weak and far away from the borders of France. Moreover, The Great Army needed to have newly occupied territories under its rule and to maintain Paris’ hegemony in these regions of Europe, and to strengthen it using Polish armed forces. The approval of the Polish society was one of the most important factor that was responsible for the negotiations concerning the rebirth of the Polish independent State. In the Polish social common consciousness there is an opinion that the rebirth of Polish statehood created by Napoleon in the shape of the Duchy of Warsaw was started on 22 July 1807. On that day the creation of a new state was proclaimed. Nevertheless, the date of the creation of the new slate is quite debatable. In June 1807 the founding stone of the nation was the creation of the structures of the Polish state. The breakthrough was in the autumn of 1806 when, during his victorious war campaign, Bonaparte defeated the Prussian Army, and on 27 October he entered Berlin. Then it was agreed upon that the rebirth of the Polish state was possible with the help of the powerful Napoleonic France. The pro-French attitude of Polish society was the result of its experience with the Russians’ and the Prussians’ solutions for "the Polish Question” that brought only disappointment. It is to be noted that in the contemporary history of Europe the changes made during the dictatorship rule of Napoleon were visible in a broader scope. The triumphal march of the invincible Great Army led by ‘the God of war’ in the region of Central and Eastern Europe was the fact that made Poles believe in regaining of Poland’s independence. Towering genius of Corsican conquered entirely Europe. People admired him and praised him as saviour of the patria and this opinion is undoubtedly true. It is worth highlighting the fact that with the fall of the Commonwealth the Polish administration was almost completely destroyed and after 12 years of state’s non-existence there was a beginning of reconstruction the Polish administration’s structure on the basis of the remnants of the Prussian administration. National institutions introduced in the period of the Governing Commission (brought into being by Napoleon on 14 January 1807 and functioning as the chief governing body and having executive rights) became one of the essential elements in creating the Duchy of Warsaw. There were some changes after the introduction of the constitution of the Duchy of Warsaw, whose purpose was to modify the structures that had been previously created in the years of the Commission (dissolved on 5 October 1807). Since then the state structure which had been created survived not only the times of the Duchy of Warsaw but also to some extent functioned till the years of the Polish Kingdom, namely between 1815-1831. The modification of ‘Poland invaded by the Prussian king’ (as the area under the power of the Commission was commonly called till July 1807) into the Duchy of Warsaw enabled Poles to maintain their national feeling with its own parliament, army, judiciary system, public administration, education and Polish as an official language throughout the life of two Polish generations.